Nephroprotective effects of ethanolic extract of Ganoderma lucidum against diethylene glycol-induced acute kidney injury in rats - Hernayanti; Hameda Dhaka Kusuma Taufiq (Indonesian Society for Biochemistry and Molecular Biology, 2025)
Background: Diethylene glycol (DEG) contamination in pharmaceutical preparations has caused numerous cases of acute kidney injury, particularly in pediatric populations. Current treatments are expensive and not readily accessible in resource-limited settings. Ganoderma lucidum, a medicinal mushroom rich in triterpenoids, flavonoids, and ergothioneine, may offer a natural therapeutic alternative. Objective: This study evaluated the nephroprotective potential of ethanolic G. lucidum extract against DEG-induced acute kidney injury in rats. Methods: Twenty-four male Wistar rats were divided into six groups: healthy control, DEG-induced control (5 g/kg BW), three G. lucidum treatment groups (250, 500, 750 mg/kg BW for 7 days plus DEG), and fomepizole control (5 mg/kg BW plus DEG). Renal function markers (β2-microglobulin, malondialdehyde) and electrolytes (sodium, potassium, chloride) were measured on day 11. Results: DEG significantly elevated β2-microglobulin (0.73 vs. 0.29 ng/mL) and malondialdehyde levels (3.368 vs. 0.72 μmol/L) while reducing electrolytes. G. lucidum extract at 500 and 750 mg/kg BW significantly improved all parameters, achieving efficacy comparable to fomepizole (p > 0.05). Conclusion: Ethanolic G. lucidum extract demonstrates significant nephroprotective effects against DEG-induced kidney injury, with 500 mg/kg BW as the optimal therapeutic dose.